Logos-Mythos-Ethos: Heidegger's Dweller and Lopez's Arctic Dreams - Pasco, Marc Oliver D (Archīum Ateneo, 2019)
This paper tries to shed light upon Martin Heidegger's thoughts concerning the crisis of homelessness which the thinker calls THE plight. Heidegger's insights concerning language guide the course of the exposition. Aside from Heidegger, it examines Barry Lopez's book Arctic Dreams, specifically the chapter entitled "The Country of The Mind" as a complementary resource for grounding the main points discussed in the paper. It is an exposition concerned with the relationship between logos, ethos, and mythos. The paper is a reflection on the relationship between these three words, which can hopefully provide a compass, resting neither simply on an axiology nor an occidental or oriental metaphysics, that may serve as a guide in gaining a renewed ethical way of being in the world. Ultimately, it shows that the questions which have been confronted by environmental ethics is essentially the question concerning our response to the primordial givenness of our place in the fourfold and our hearing of the silent voice of language.